log(4x+1)+log(x+2)=1

Simple and best practice solution for log(4x+1)+log(x+2)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(4x+1)+log(x+2)=1 equation:


Simplifying
log(4x + 1) + log(x + 2) = 1

Reorder the terms:
glo(1 + 4x) + log(x + 2) = 1
(1 * glo + 4x * glo) + log(x + 2) = 1
(1glo + 4glox) + log(x + 2) = 1

Reorder the terms:
1glo + 4glox + glo(2 + x) = 1
1glo + 4glox + (2 * glo + x * glo) = 1
1glo + 4glox + (2glo + glox) = 1

Reorder the terms:
1glo + 2glo + 4glox + glox = 1

Combine like terms: 1glo + 2glo = 3glo
3glo + 4glox + glox = 1

Combine like terms: 4glox + glox = 5glox
3glo + 5glox = 1

Solving
3glo + 5glox = 1

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Reorder the terms:
-1 + 3glo + 5glox = 1 + -1

Combine like terms: 1 + -1 = 0
-1 + 3glo + 5glox = 0

The solution to this equation could not be determined.

See similar equations:

| 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= | | 4t^2-28t+45=0 | | 8s-(5s+6)=.5(20+6) | | 6(7b+6)-(b+5)=-10 | | -.25x-2= | | E=5r+18 | | -4.75+2.19= | | +13-(+18)= | | 5.5=2+d | | 6(L+2)=36-6L | | 10-3x=-3(x-4) | | 13-18= | | 5(L+2)=36-5L | | 2y+15=19 | | -6.47-10.16= | | 4x^2+3=-18x | | +0-(+12)= | | ((5)/(2x+4)+4)=((-1)/(x+2)) | | 1=x+23 | | 6x+3=x-6 | | 5y+2(y-4)=5(y+1)-2 | | 4(y+1)+5=(y-1)+y | | -3x-6y=17 | | 6x+10=x+25 | | 8x-(2x+4)=38 | | z+15=20 | | -2(n-1)=3-2n | | 5x+2=x-2 | | h/-19=-10 | | 156=-5x-4(4x+3) | | 87=3(1-4r) |

Equations solver categories